Rural livelihoods under prolonged conflict: Evidence from a panel household survey in Sudan - Nigus, Halefom Yigzaw; Abushama, Hala; Rakhy, Tarig; Mohamed, Shima; Siddig, Khalid; Kirui, Oliver K. (International Food Policy Research Institute, 2025)
This report presents evidence from the Sudan Rural Household Survey of 2023 and 2024, a two-wave panel survey that assesses how rural households are navigating prolonged conflict. By tracking the same households over time, the survey provides longitudinal insights into livelihoods, food security, access to markets and productive resources, and exposure to shocks across an insecure and rapidly evolving context. The findings from the survey data analysis point to an uneven pattern of economic adjustment by households rather than sustained recovery. Rural households are actively adapting through changes in livelihood strategies, income diversification, and increased participation of household members in income-generating activities. Compared to 2023, fewer households reported in 2024 having no employment. Engagement in salaried work and agriculture also rose. Despite these shifts, income losses remain widespread. Only a small share of households reported improved earnings in 2024, indicating that adaptation is largely driven by necessity rather than durable recovery. Food consumption outcomes improved markedly between survey waves, with substantial declines in the share of households in 2024 reporting poor or borderline diets. At the same time, experience-based measures show that food insecurity remains pervasive, with more than half of rural households facing moderate or severe food insecurity. There has been little change in the prevalence of severe food insecurity. The continuing food insecurity challenges underscore the fragility of recent gains and the continued vulnerability of many households.